Corporate political activism and information transfers - Dane M. Christensen; Hengda Jin; Joshua A. Lee; Suhas A. Sridharan; Laura A. Wellman (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
Prior research suggests that: (1) politically active firms have an information advantage over firms that do not engage in the political process, but also that (2) politically active firms are more likely to disclose policy-related information. We examine whether there are externalities associated with the processing of political information by politically active firms. We study this question in the setting of intra-industry information transfers around earnings announcements. Measuring firms' political activism using campaign contributions, we find stronger intra-industry information transfers from politically active firms to their industry peers. These information transfers are stronger when there is more discussion during conference calls of political topics that have industry or market-wide implications. Similarly, these information transfers are also stronger when there is greater political uncertainty. Our paper highlights an important information externality related to politically active firms' disclosures and improves our understanding of how politically active firms affect their industries' information environment.
Keywords: D72; M41; M48; 330; Information transfer; earnings announcements; political economy